Pelatihan Sistem Informasi Penjualan Rotan Bagi Pelaku Rotan Tegalwangi - Martanto; Nana Suarna; Willy Prihartono (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Tegalwangi rattan industry, as one of the traditional industries with high cultural value, faces various challenges in the era of globalization. One proposed solution is the training in the use of rattan sales information systems to enhance the competitiveness and efficiency of this industry. This Community Engagement aims to analyze the situation of the rattan industry in Tegalwangi, identify the challenges it faces, and design a community engagement approach to help address these issues. The training has brought significant benefits to rattan business operators in Tegalwangi. With the implementation of the Rattan Sales Information System, they can optimize the sales process, improve operational efficiency, and expand their market reach. This system also enables them to be more responsive to customer demands and needs. Additionally, training participants have gained a deeper understanding of information technology and how to apply it to their businesses. They have learned how to manage sales data more effectively, analyze sales trends, and make decisions based on accurate and up-to-date information. With this training, rattan business operators in Tegalwangi become more competitive in an increasingly competitive market. They can compete more effectively through the improvement of service quality and products, as well as adaptation to technological advancements.